Barriers to and facilitators of rehabilitation according to socio-economic status, after acute respiratory distress syndrome due to COVID-19: A qualitative study in the RECOVIDS cohort - Mathilde Kléber; Nicolas Meunier-Beillard; Isabelle Fournel; Elea Ksiazek; Marine Jacquier; Fiona Ecarnot; Jean-Philippe Rigaud; Pierre-Louis Declerq; Jean-Pierre Quenot; Marie Labruyère (PLoS ONE, 2025)
Background The COVID-19 pandemic may have compounded social disparities in access to healthcare, with possible deleterious consequences on the functional prognosis of patients after a stay in the intensive care unit (ICU). In the previous RECOVIDS study, we reported that despite comparable pulmonary sequelae and similar access to rehabilitation, socio-economically “vulnerable” patients had lower quality of life at 6 months after an ICU stay. We aimed to describe the barriers to, and facilitators of participation in rehabilitation, among patients from the RECOVIDS study, regardless of their socio-economic situation. Methods Qualitative study using semi-structured interviews with adult patients admitted to ICU for PCR-proven SARS-CoV-2 infection, and who had acute respiratory distress syndrome (ARDS) or had received high flow nasal oxygen. In addition, patients had to have been living at home for the month prior to the interview and had to be proficient in French. Eligible patients were randomly selected, aiming to select the same number of socially deprived and non-socially-deprived patients. Interviews were transcribed for thematic analysis. Results In total, 31 interviews were performed from 10/2021 to 01/2022; 16 with socially deprived, and 15 with non-deprived participants. Average age was 65.2 (±11.6) years. Four themes emerged from the analysis of the interviews, namely: (1) the impact of the patient’s professional and socio-economic situation; (2) the feeling that age and socio-economic situation influence access to rehabilitation; (3) a perception that the healthcare system was saturated, and that inequalities exist in access to rehabilitation resources; (4) perception of previous own health and expectations of post-resuscitation health status. Conclusion A precarious socio-economic situation has a substantial impact on access to rehabilitation after ICU admission for ARDS caused by COVID-19. It represents a barrier to rehabilitation through the combined action of various social determinants that deserve to be detected early, in order to take appropriate action to ensure that the most socially vulnerable individuals can benefit from access to rehabilitation.